The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jdv.14066
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A for severe atopic dermatitis in children. efficacy and safety in a retrospective study of 63 patients

Abstract: Our data confirm that CSA is efficacious and acts rapidly in the majority of children with severe AD. CSA therapy can provide sustained remission in some patients. CSA seems to be well tolerated in children, but strict monitoring is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 23 publications
(76 reference statements)
0
32
1
Order By: Relevance
“…Zaki used the highest dosing of the pediatric trials, at 5‐6 mg/kg, followed by Harper and Berth‐Jones with 5 mg/kg daily, titrated to clinical response. Hernandez‐Martin used a mean initial dose of 4.3 mg/kg. Sarıcaoğlu and Bunikowski used 2.5‐5 mg/kg daily and 2.5 mg/kg, respectively, initially, also titrated to clinical response, and Garrido Colmenero used weekend dosing—5 mg/kg given Saturday and Sunday only.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Zaki used the highest dosing of the pediatric trials, at 5‐6 mg/kg, followed by Harper and Berth‐Jones with 5 mg/kg daily, titrated to clinical response. Hernandez‐Martin used a mean initial dose of 4.3 mg/kg. Sarıcaoğlu and Bunikowski used 2.5‐5 mg/kg daily and 2.5 mg/kg, respectively, initially, also titrated to clinical response, and Garrido Colmenero used weekend dosing—5 mg/kg given Saturday and Sunday only.…”
Section: Resultsmentioning
confidence: 99%
“…Berth‐Jones, Sarıcaoğlu, and Garrido Colmenero all reported no incidence of clinically significant creatinine rise, while Harper, Yee, and Zaki reported 9.3%, 7%, and 5%, respectively. El‐Khalawany reported that 15% of participants developed renal dysfunction; Bunikowski reported 10% had a rise in creatinine (not otherwise defined); and in Hernandez‐Martin's cohort, 3% had a transient rise in urea nitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations